Central Respiration and Mechanical Ventilation in the Gating of Swallow With Breathing - Horton, Kofi-Kermit; Segers, Lauren S.; Nuding, Sarah C.; O’Connor, Russell; Alencar, Pierina A.; Davenport, Paul W.; Bolser, Donald C.; Pitts, Teresa; Lindsey, Bruce G.; Morris, Kendall F.; Gestreau, Christian (Frontiers in Physiology, 2018)
Swallow-breathing coordination safeguards the lower airways from tracheal aspiration of bolus material as it moves through the pharynx into the esophagus. Impaired movements of the shared muscles or structures of the aerodigestive tract, or disruptions in the interaction of brainstem swallow and respiratory central pattern generators (CPGs) result in dysphagia. To maximize lower airway protection these CPGs integrate respiratory rhythm generation signals and vagal afferent feedback to synchronize swallow with breathing. Despite extensive study, the roles of central respiratory activity and vagal feedback from the lungs as key elements for effective swallow-breathing coordination remain unclear. The effect of altered timing of bronchopulmonary vagal afferent input on swallows triggered during electrical stimulation of the superior laryngeal nerves or by injection of water into the pharyngeal cavity was studied in decerebrate, paralyzed and artificially ventilated cats. We observed two types of single swallows that produced distinct effects on central respiratory-rhythm across all conditions: post-inspiratory type swallows disrupted central-inspiratory activity without affecting expiration, whereas expiratory type swallows prolonged expiration without affecting central-inspiratory activity. Repetitive swallows observed during apnea reset the E2 phase of central respiration and produced facilitation of swallow motor output nerve burst durations. Moreover, swallow initiation was negatively modulated by vagal feedback and was reset by lung inflation. Collectively, these findings support a novel model of reciprocal inhibition between the swallow CPG and inspiratory or expiratory cells of the respiratory CPG where lung distension and phases of central respiratory activity represent a dual peripheral and central gating mechanism of swallow-breathing coordination.